1996
DOI: 10.1017/s1357729800014302
|View full text |Cite
|
Sign up to set email alerts
|

Performance and blood chemistry in lambs following fasting and transport

Abstract: Thirty-six 5-month-old Dorset ram lambs (28·7 kg) were used to investigate the effects of fasting and transport on performance and selected blood parameters. Three treatment groups (no. = 12) were: (1) control-food and water, without transport; (2) fasting for 72 h, without transport; and (3) transport in a trailer to a nearby auction-barn, then driven 8 h/day for 3 days without food or water for a total of 72 h. Lambs were given a total mixed diet containing 163 g/kg crude protein throughout the 28-day post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…This is an indicator of prolonged lack of food (Horton et al, 1996;Knowles et al, 1996), or indeed starvation, in which functional body tissue is being utilised (Broom and Fraser, 2007). Knowles et al (1993Knowles et al ( , 1995Knowles et al ( , 1998 transported lambs for 9, 14 and 24 h and ewes for 24 h and found that after each journey there was an increase in the plasma concentration of β-hydroxybutyrate.…”
Section: Resultsmentioning
confidence: 99%
“…This is an indicator of prolonged lack of food (Horton et al, 1996;Knowles et al, 1996), or indeed starvation, in which functional body tissue is being utilised (Broom and Fraser, 2007). Knowles et al (1993Knowles et al ( , 1995Knowles et al ( , 1998 transported lambs for 9, 14 and 24 h and ewes for 24 h and found that after each journey there was an increase in the plasma concentration of β-hydroxybutyrate.…”
Section: Resultsmentioning
confidence: 99%
“…The transport effects on plasma glucose reported from other studies are highly controversial (reviewed by Horton et al, 1996), maybe due to differences in road construction and mode of driving. The response in lactate and NEFA resembled the kind and speed of alteration found in cows subjected to draught work (Zerbini et al, 1995).…”
Section: Effects Of Transportmentioning
confidence: 99%
“…Metabolic changes may be exaggerated by the additional energy demands during transportation associated with maintaining posture in a moving vehicle and thermoregulation in unfavourable conditions (Lawrence et al 2004). Some studies that have separated the effects of fasting alone from the combined effects of fasting and transport in lambs have generally been unable to demonstrate that transport is a significant additional stressor (Warriss et al 1990;Knowles et al 1995;Broom et al 1996), while others suggest transport exacerbates the fasting liveweight loss (Thompson et al 1987;Horton et al 1996).…”
Section: Faecal and Urinary Wastementioning
confidence: 99%